Identifying and Addressing the Determinants of Stunting in the First 1000 Days: Review of Nutrition Governance Strategies and Implementation of the Philippine Plan of Action for Nutrition (PPAN) 2017–2022 - Maria Asuncion A. Silvestre; Christian Edward L. Nuevo; Alfredo Jose C. Ballesteros; Joy Bagas; Valerie Gilbert Ulep (Philippine Institute for Development Studies (PIDS), 2023)
To examine whether current strategies and investment are directed towards cost-effective interventions, we reviewed public expenditures on nutrition (Annual Investment Plans [AIPs] and Gender and Development [GAD)] budgets) and evaluated implementation of the Philippine Plan of Action for Nutrition (PPAN 2017-2022) at regional to barangay levels. The delivery and management of mostly nutrition sensitive programs and interventions by looking at the three dimensions of awareness, adoption, and accountability. Qualitative data collection through KIIs was undertaken for Objective 3a (LGU nutrition governance) and Objective 3b (PPAN assessment) in an integrated manner. Eight (8) KIIs were conducted at regional, 9 at provincial, and 26 at city/municipality levels and 104 interviews were conducted at the barangay level from January to March 2021. Higher levels of governance (regional to city/municipality levels are cognizant of the PPAN (2017-2022) as the national strategy to improve nutrition. Integral to the Philippine Development Plan; considered as a roadmap for operationalizing programs, projects, and activities. At these levels, the PPAN framework is integrated in local nutrition action and investment plans. However, there is a general lack of awareness on the PPAN at the barangay level which is the locus of implementation. Budget allocation and implementation are found to be inconsistent and highly fragmented across different governance levels. At lower LGU levels financing nutrition programs are perceived to be highly dependent on the priority of and buyin from local chief executives, particularly mayors. This disparity in funding across LGUs is highly indicative of a lack of specific guidance for budget allocation. Local nutrition committees need to prioritize programs and target beneficiaries given the already limited budget. A deficit in human resources especially at the city/municipality and barangay levels remains to be a major bottleneck in implementation. Regional NNC Offices serve as a conduit for accountability and reporting between national level and LGUs. They are also responsible for advocating resource generation and mobilization, as well as building linkages. The MELPPI is done to track program implementation. Provinces function as intermediaries between LGUs and different stakeholders through advocacy, strategy development, and overall knowledge brokering. Cities and municipalities, on the other hand, are the primary drivers of implementation. They craft and develop the local nutrition action plans and provide support to barangays which are at the forefront of implementation. At their level, they perform program implementation review (PIR) to assess accomplishment of targets, and programmatic performance based on nutrition outcomes evidenced by OPT results - the main data for reporting prevalence of different forms of malnutrition and overall nutritional status. Results helped inform a proposed evidence-based framework for the comprehensive and sustainable implementation of the First 1000 Days Strategy and Nurturing Care framework for Early Child Care and Development.
Keywords: 330; nutrition governance; plan of action for nutrition; awareness; adoption; accountability; First 1000 Days; Nurturing Care